Social capital and healthy eating among two ethnic minority groups in Yunnan Province, Southwest China: the mediating role of social support and nutrition knowledge - Zhang, Qiang; Huangfu, Chunrong; Wan, Qingqing; Su, Weiwei; Zhu, Xiao; Yu, Bin; Min, Xiangdong; Liu, Zhitao (Frontiers in Nutrition, 2024)
Background: Although social capital has been linked to dietary intake particularly in disadvantaged populations, little is known about the mechanisms. This study aimed to investigate whether social support (SS) and nutrition knowledge (NK) mediate the association between social capital and healthy eating habits.Methods: A probability sample of two ethnic minority groups in Yunnan Province, Southwest China were included (n=1033, mean age 47.5±14.7 years). Bonding and bridging social capital (BOC and BRC) were assessed with the Personal Social Capital Scale (PSCS-16). Dietary data were evaluated with the Chinese Healthy Eating Index (CHEI), a measure of diet quality which reflects adherence to the Chinese Dietary Guidelines. NK and SS were measured with a validated questionnaire and scale, respectively. Structural Equation Modelling was used to calculate the direct, indirect and total effects of social capital on CHEI scores.The mean score of CHEI was 57.4±9.8, which was significantly lower in men and older people. Low adherence to dietary guidelines were to observed in the consumption of dairy, beans, nuts, animalsource food vegetables and fruits. BOC and BRC were positively associated with CHEI score (β=0.37 and 0.38, all P<0.05). Social support and nutrition knowledge mediated 45.9% and 39.5% of the total effect of social capital on CHEI score, respectively.Conclusion: social capital appears to enhance adherence to dietary guidelines by improving nutrition knowledge and social support. Nutrition promotion programs therefore should consider incorporating strategies that foster social capital development, particularly in disadvantaged populations.